Multi-disciplinary orthodontic camouflage treatment of a severe skeletal class III malocclusion with 1 year follow-up - A case report - Moina K Adeni; Ratna Parameswaran; Devaki Vijayalakshmi; Junaid Sainulabdeen (Wolters Kluwer Medknow Publications, 2022)
Rationale: Orthodontic camouflage serves its purpose in treating mild to moderate skeletal dysplasia and in conditions where the patient is reluctant to opt for orthognathic surgery or when it is contraindicated. Patient Concerns: A 22-year-old male was concerned about his irregular teeth. Diagnosis: Angle's dentoalveolar class III malocclusion on class III skeletal on an average mandibular plane angle with anterior crossbite, deep bite, crowding in maxillary and mandibular anteriors, proclined maxillary anteriors and retroclined mandibular anteriors with reverse overjet and congenitally missing 12, 22, palatally impacted 13 and retained deciduous 63 and palatally placed 23. Treatment: Orthodontic camouflage with a multi-disciplinary approach. Outcome: Optimal functional and dentofacial aesthetics were achieved by 22 months. Take-Away Lesson: The limitations of camouflage must be kept in mind and explained to the patient. The biomechanics need to be customized and integrating different specialties helps maximize the treatment benefits.